PENGARUH THEORY OF PLANNED BEHAVIOR DAN LITERASI KEUANGAN TERHADAP KEPUTUSAN PENGGUNAAN PAYLATER PADA GENERASI Z - Raditya Ferdianto; Ikhwan Nurfatih (PT. Hasba Edukasi Mandiri, 2026)
The emergence of digital financial services has triggered an increase in the popularity of paylater payments, especially among tech-savvy Generation Z. This problem has made it necessary to comprehend the elements that affect people's decisions to utilize paylater, particularly students. The goal of this study is to examine how financial literacy and the Theory of Planned Behavior (TPB) affect Generation Z's decision to utilize paylater at Pamulang University. Students who had utilized the paylater payment system completed questions as part of a quantitative survey methodology. Multiple linear regression was used to analyze the data. The study's findings show that while financial literacy promotes more logical decision-making, elements of the Theory of Planned Behavior have a substantial impact on paylater use decisions.